2007
DOI: 10.1016/j.febslet.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Afr1p has a role in regulating the localization of Mpk1p at the shmoo tip in Saccharomyces cerevisiae

Abstract: Afr1p functions to promote adaptation to pheromoneinduced growth arrest and morphogenesis. We show here that Afr1p regulates polarized localization of the Mpk1p MAP kinase in shmooing cells. Deletion of AFR1 results in mislocalization of Mpk1p although the scaffold protein Spa2p localizes normally at shmoo tip, and overexpression of Spa2 cannot rescue this defect, indicating Afr1p in required for Spa2p to recruit Mpk1 to the site of polarized growth during mating. Overexpression of SPA2 partially suppresses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We therefore undertook a systematic, high-throughput analysis of alpha factor-induced changes in protein localization of GFP-tagged yeast strains. It should be noted that a comprehensive survey of proteins localized to the shmoo tip has not previously been carried out despite many studies that have implicated key roles for individual proteins in this dynamic cellular compartment. Building on our previous success in constructing and screening yeast cell microarrays, we screened the collection of GFP-tagged yeast strains for pheromone-induced changes in protein localization.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore undertook a systematic, high-throughput analysis of alpha factor-induced changes in protein localization of GFP-tagged yeast strains. It should be noted that a comprehensive survey of proteins localized to the shmoo tip has not previously been carried out despite many studies that have implicated key roles for individual proteins in this dynamic cellular compartment. Building on our previous success in constructing and screening yeast cell microarrays, we screened the collection of GFP-tagged yeast strains for pheromone-induced changes in protein localization.…”
Section: Resultsmentioning
confidence: 99%
“…However, the protein or proteins that mediate pheromone activation of the cell integrity pathway have not been identified. A recent study demonstrated that Afr1p is required for concentrating Slt2p in the mating projection in response to mating pheromone, although it failed to detect a noticeable change in Slt2p activity in cells lacking Afr1p (Changwei et al ., 2007). Because of the strong correlations between Afr1p and Slt2p with respect to their role in promoting α‐factor resistance, we reinvestigated Slt2p activation in AFR1 deletion and AFR1 overexpression cells by immunoblot analysis using an anti‐p44/42 MAPK antibody that specifically recognizes the doubly phosphorylated form of Slt2p (Giot & Konopka, 1997; Davis et al ., 1998).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that both septins and Afr1p act together as a barrier at the neck of mating projection to prevent diffusion of pheromone pathway components from the projection tip and restrict the active zone of pheromone signaling to the tip of mating projection (Douglas et al ., 2005). Because Afr1p is also required for localization of Slt2p to the tip of mating projection (Changwei et al ., 2007), where its two upstream functionally redundant MEKs, Mkk1p and Mkk2p, also localize (van Drogen & Peter, 2002), it is applaudable to propose that Afr1p acts as a barrier to restrict, in addition to components of the pheromone signaling pathway, Slt2p to the tip of mating projection for activation by Mkk1p and Mkk2p. Alternatively, Afr1p may function as a scaffold‐like protein or a platform at the base of mating projections to recruit Slt2p to the projection tip and place Slt2p in close proximity to Mkk1p and Mkk2p for activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations